Razvojno analitični pogled na narcisizem - Matjan, Polona (Psihološka obzorja (Ljubljana), 2009)
Narcissistic pathology is connected to the pathology of the self. This articla makes an overview of definitions of developmental analytic theories and stops with Kohut, Kernberg, Masterson, Auerbach and Mollon. The self is understood as a separate personality structure and has its own developmental line. Narcissism is a personality disorder that has its roots in preodipal development phases, mostly in the practicing and rapprochment subphase and in the oedipal phase as well. Recent research shows that the oedipal phase and the relation between the mother, the child's father (or the partner in general) and the child is crucial for the maintainance of the pathological narcissism. Mothers who do not believe in a satisfying relationship with a man in general, keep the child in the dyadic position and do not support the development of the child's own identity.
Keywords: grandiozni self; self; omnipotentnost; narcisizem; separacija; individualizacija; psihoanaliza